(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
The article presents the results of a study of the effects of improving the accuracy of strikes in young tennis players against the background of the aftereffect of a short-term vestibular load during the experiment. It was found that in young tennis players of the EG, which trained according to the experimental program, the number and accuracy of strikes for 30 seconds were accompanied by a pronounced increase in their level by the end of the 10-month experiment, while in the CG, which trained according to the traditional program, such positive shifts in the sphere of the studied parameters were not noted